Synthesis and characterization of electrospun fibers from PAN/cellulose acetate: a suitable approach - Mat Nong, Mohd Ali; Md Yusof, Juraina; Ismail, Ismayadi; Ab Ghani, Mohd Hafizuddin; Che Abdullah, Che Azurahanim (Faculty of Engineering, Universiti Putra Malaysia, 2024)
Electrospun nanofibers derived from Polyacrylonitrile (PAN) and Cellulose Acetate (CA) were successfully synthesized using the electrospinning technique. The morphology of these nanofibrous was examined through Field Emission Scanning Electron Microscopy (FESEM), providing invaluable insights into their structural characteristics and prospective applications. Elemental composition and chemical properties of the nanofibers were thoroughly investigated via energy-dispersive X-ray spectroscopy (EDX). Results demonstrated an elemental ratio of 67.03% carbon (C) and 32.97% nitrogen (N) in the PAN fibers, while the CA composite fibers exhibited elemental ratios of 63.20% C, 26.31% N, and 10.49% oxygen (O). These findings underscore the potential utility of cellulose nanofibers across a myriad of disciplines, encompassing environmental remediation, energy storage, and biomedical engineering.